Advancing Ticagrelor Bioavailability: A Comprehensive Review of Solubility Enhancement Techniques - Tania Miranda Sarlie; Rachmat Mauludin; Saleh Wikarsa; Yuda Prasetya Nugraha; Muhammad Luthfi Shidik (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Ticagrelor (TICA) inhibits platelet activity by reversibly binding to the P₂Y₁₂  receptor, it is classified as a BCS class IV drug with low solubility and permeability. BCS Class IV drugs have a major challenge due to their reduced rate of dissolution, which leads to poor bioavailability. The absolute bioavailability of TICA after oral administration is ~36%. Various techniques, including particle size reduction, solid dispersion, lipid-based formulation, co-crystals, and polymeric micelles can increase solubility. This article discusses the methodology used to increase the solubility of ticagrelor, thereby emphasizing the research that has been conducted and documented. The increased bioavailability of ticagrelor is apparent when formulated as a solid dispersion (SD), self- microemulsifying drug delivery system (SMEDDS), self-nanoemulsifying drug delivery system (SNEDDS), nanostructured lipid carriers (NLC), suspensions, and co-crystals. Among these approaches, co-crystals and solid dispersions are highly recommended for improving the solubility of ticagrelor. This review provides insights into formulation strategies for improving ticagrelor solubility, guiding future research on its bioavailability and efficacy